Multiparametric Profiling of Single Nanoscale Extracellular Vesicles by Combined Atomic Force and Fluorescence Microscopy: Correlation and Heterogeneity in Their Molecular and Biophysical Features. Issue 14 (7th March 2021) - Cavallaro, Sara; Pevere, Federico; Stridfeldt, Fredrik; Görgens, André; Paba, Carolina; Sahu, Siddharth S.; Mamand, Doste R.; Gupta, Dhanu; El Andaloussi, Samir; Linnros, Jan; Dev, Apurba
Abstract: Being a key player in intercellular communications, nanoscale extracellular vesicles (EVs) offer unique opportunities for both diagnostics and therapeutics. However, their cellular origin and functional identity remain elusive due to the high heterogeneity in their molecular and physical features. Here, for the first time, multiple EV parameters involving membrane protein composition, size and mechanical properties on single small EVs (sEVs) are simultaneously studied by combined fluorescence and atomic force microscopy. Furthermore, their correlation and heterogeneity in different cellular sources are investigated. The study, performed on sEVs derived from human embryonic kidney 293, cord blood mesenchymal stromal and human acute monocytic leukemia cell lines, identifies both common and cell line‐specific sEV subpopulations bearing distinct distributions of the common tetraspanins (CD9, CD63, and CD81) and biophysical properties. Although the tetraspanin abundances of individual sEVs are independent of their sizes, the expression levels of CD9 and CD63 are strongly correlated. A sEV population co‐expressing all the three tetraspanins in relatively high abundance, however, having average diameters of <100 nm and relatively low Young moduli, is also found in all cell lines. Such a multiparametric approach is expected to provide new insights regarding EV biology and functions, potentially deciphering unsolved questions in this field. Abstract : Extracellular vesicles (EVs) offer unique opportunities for both diagnostics and therapeutics. In this paper, the advantages of using a combined fluorescence and atomic force microscopy for multiparametric profiling of single small EVs (sEVs) are presented. By studying and correlating membrane protein compositions, size, and mechanical properties of single sEVs, the platform can provide new insights about EV subpopulations and heterogeneity.